Zoonotic bacteria research and analysis of antimicrobial resistance levels in parrot isolates from pet shops in the city of Fortaleza, Brazil - Marques,Adson R. (2021)
ABSTRACT: The Psittaciformes are among the most popular pets due to their intelligence, ability, and ease of maintenance in small environments. However, the absence of adequate environmental stimuli generated by confinement can predispose these animals to characteristic stress conditions, leaving them susceptible to the triggering of various diseases, among which those of bacterial origin stand out. The objective of this study was to carry out a survey of enterobacteria and evaluate the antimicrobial sensitivity profile of bacteria isolated from parrots from a pet shop in the city of Fortaleza, Ceará. Ninety-six samples were collected from four pet shops (which were classified as A, B, C and D), eight samples of local swabs from budgerigar (Melopsittacus undulatus), were collected from each establishment eight from cockatiels (Nymphicus hollandicus) and eight from lovebirds (Agapornis sp.). Isolation of enterobacteria is under the methodology used by Lopes et al. (2015) with modifications. The method used to study bacterial resistance was the Kirby-Bauer method, following the standards stipulated by the Clinical and Laboratory Standards Institute. Sixty-eight enterobacteria strains from ten different species, Proteus mirabilis, Citrobacter diversus, Pantoea agglomerans, Escherichia coli, Providencia stuartii, Hafnia alvei, Proteus vulgaris, Serratia liquefaciens, Enterobacter sakasakii and Citrobacter amalonaticus, were isolated. P. agglomerans was the bacterium with the highest frequency of isolates from pet shop parrots, making up 23.5% of the isolates; the second-most isolated strain was P. mirabilis with 17.7%. In this study, 79% of the isolated strains were resistant to at least one class of antimicrobials tested. Tetracycline proved to be the most resistant antimicrobial (44%), followed by polymyxin B (38%) and nalidixic acid (25%). Among the 68 strains, 19% did not show resistance to any of the classes of antimicrobials tested. The condition of multidrug resistance - resistance to ≥3 classes of antimicrobials - was observed in 18% of the isolated strains.